1972
DOI: 10.1051/forest/19720302
|View full text |Cite
|
Sign up to set email alerts
|

Quelques aspects de la variabilité infraspécifique du Douglas (Pseudotsuga menziesiiMirb) introduit en zone méditerranéenne subhumide

Abstract: RÉSUMÉL'expérience, dont les résultats sont décrits ici, fait partie du programme général d'étude de la variabilité infraspécifique du Douglas. La situation de cet essai comparatif de provenances dans les Maures, en zone méditerranéenne subhumide, ainsi que l'étude de sources de graines californiennes, en font son originalité.Bien que les observations ne concernent qu'un stade juvénile, il est possible de mettre en évi-dence de nombreuses différences entre provenances pour des caractères phénologiques, de vigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Significant differences among provenances have been detected for all wood density variables as well as for basal area and for growth reduction during extremely dry years. The observed differences among provenances were consistent with genetic differences previously reported for growth, morphology, and phenology in Douglas-fir (Birot and Ferrandes 1972;Ching and Hinz 1978;Christophe and Birot 1979;White 1987). In a few cases, it has been suggested that these variations are related to environmental or climate causes (Sweet 1965;Irgens-Moller 1968;St Clair et al 2005).…”
Section: Contrasting Behaviour Among Provenances During Dry Yearssupporting
confidence: 90%
“…Significant differences among provenances have been detected for all wood density variables as well as for basal area and for growth reduction during extremely dry years. The observed differences among provenances were consistent with genetic differences previously reported for growth, morphology, and phenology in Douglas-fir (Birot and Ferrandes 1972;Ching and Hinz 1978;Christophe and Birot 1979;White 1987). In a few cases, it has been suggested that these variations are related to environmental or climate causes (Sweet 1965;Irgens-Moller 1968;St Clair et al 2005).…”
Section: Contrasting Behaviour Among Provenances During Dry Yearssupporting
confidence: 90%